2021
DOI: 10.1111/fwb.13683
|View full text |Cite
|
Sign up to set email alerts
|

A manipulative field experiment reveals the ecological effects of invasive mosquitofish (Gambusia affinis) in a tropical wetland

Abstract: The mosquitofish (Gambusia affinis: Poeciliidae) is one of the world's most widespread invaders, but our ability to predict the consequences for native species in the tropics is limited by a paucity of research and a lack of knowledge of how environmental factors influence mosquitofish impacts. We undertook a field experiment using cages to manipulate mosquitofish densities in a Hong Kong wetland during the warm wet season and the cool dry season. We measured fish effects on invertebrates and periphyton, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 95 publications
0
1
0
Order By: Relevance
“…Nonetheless, management strategies to reduce the spread of exotics are needed. Although poeciliids have no effect on native fish communities in Hong Kong, they have been confirmed to impact local amphibians (Karraker et al., 2010) and invertebrates (Tsang & Dudgeon, 2021a, 2021b). Poeciliids have been reported to impact indigenous fishes elsewhere by means of aggression (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, management strategies to reduce the spread of exotics are needed. Although poeciliids have no effect on native fish communities in Hong Kong, they have been confirmed to impact local amphibians (Karraker et al., 2010) and invertebrates (Tsang & Dudgeon, 2021a, 2021b). Poeciliids have been reported to impact indigenous fishes elsewhere by means of aggression (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Native to the Mississippi River basin, MSQ thrives in lentic habitats and slow‐moving pools of rivers and streams (Krumholz, 1948). Studies have revealed the negative effects of MSQ on a variety of taxa ranging from small native fish (Pasbrig, 2010), amphibians (Goodsell & Kats, 1999), and invertebrates (Leyse et al., 2004; Tsang & Dudgeon, 2021). Given their major ecological impacts globally, they are listed as one of IUCN's 100 worst invasive alien species in the world (Simberloff & Rejmanek, 2019).…”
Section: Introductionmentioning
confidence: 99%